Growth and Yield of Vertical Hydroponic Lettuce under Liquid Organic Fertilizer and Shade Intensity Treatments - Ika Purnamasari; Tri Ratnasari; Berlian Cindy Febrian; Annisa Lailatus Sufiah; Bintang Kurniawan; Ummi Sholikhah; Tri Wahyu Saputra; Wildan Muhlison (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Lettuce (Lactuca sativa L.) production needs to be increased to fulfill increasing demand. Application of liquid organic fertilizer (LOF) in the hydroponic nutrient solution and adding shade to reduce solar radiation intensity are expected to improve lettuce yield. The purpose of this study was to investigate the effect of providing shade and adding LOF as a nutrient to optimize the results of hydroponic lettuce cultivation in Situbondo Regency. This study used a factorial Randomized Block Design (RBD) with UV plastic shading as a factor at different levels, namely 6% and 14%. The second factor was the nutrient composition used, namely 100% AB mix, 25% LOF + 75% AB mix, and 50% LOF + 50% AB mix. The results showed that the interaction of the two factors showed a significant difference in the chlorophyll content of plant leaves. The application of each factor was able to influence plant height, number of leaves, fresh weight, leaf area, leaf color, and crispness level, but did not affect the canopy area of lettuce plants. The use of 14% UV plastic and the addition of 25 LOF, separately resulted the highest yield of lettuce.